Description of palatal height in Balinese dentistry students of Mahasaraswati Denpasar University : Gambaran tinggi palatum pada mahasiswa kedokteran gigi suku Bali di Universitas Maharaswati Denpasar - Ketut Virtika Ayu; Wiwekowati; Ni Wayan Eka Saraswati (Makassar Dental Journal, 2021)
Background: In removable orthodontic treatment, it is also necessary to consider the retention and stability, including the height of the palate. Objective: To determine the description of the palate height in the Balinese people with the measurement method of Camila, et al. Methods: This study used an analytic observational design with a cross sectional approach. The study was conducted in Faculty of Dentistry, Mahasaraswati University Denpasar with purposive sampling technique based on inclusion criteria. The samples were dental students of batch 2017-2019 who are Balinese. Analysis of the data through the stages of nor-mality test using Kolmogorov-Smirnov, homogeneity test using Levene test, and descriptive test using Mann-Whitney U test. Results: Palatal height index of Balinese males was an average of 38.93±6.27 and females with an average of 35.05±7.10. Based on the comparative test, it was concluded that there was no significant difference in palatal height for males and females.